2004
DOI: 10.4049/jimmunol.173.4.2815
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Recruitment of Plasmacytoid Dendritic Cells in Synovial Fluid and Tissue of Patients with Chronic Inflammatory Arthritis

Abstract: Dendritic cells (DCs) are thought to play a key role in driving the immunopathogenic response underlying chronic inflammatory arthritis. In this study, we have examined the presence and phenotype of plasmacytoid DCs (pDCs) in the synovial fluids (SF) of patients with rheumatoid arthritis (RA), psoriatic arthritis (PA), and osteoarthritis (OA) and determined the chemotactic properties of SF from these patients toward pDCs. Flow cytometry analysis showed that the percentage of pDCs, identified as a population of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
81
0
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(94 citation statements)
references
References 63 publications
10
81
0
3
Order By: Relevance
“…A previous study, in which ST was immunohistochemically double-stained with mAb 12A and antiCD1a, also demonstrated that the HC gp-39-presenting cells were DC-like cells (6). Moreover, the presence of DCs in the SF of RA patients has been described (35,36).…”
Section: Discussionmentioning
confidence: 89%
“…A previous study, in which ST was immunohistochemically double-stained with mAb 12A and antiCD1a, also demonstrated that the HC gp-39-presenting cells were DC-like cells (6). Moreover, the presence of DCs in the SF of RA patients has been described (35,36).…”
Section: Discussionmentioning
confidence: 89%
“…lupus erythematosus disease, psoriasis and rheumatoid arthritis) [1,51,52], allergic diseases (i.e. contact dermatitis and nasal mucosa polyps) [53] and in tumors [2,54] (Table 1).…”
Section: Reviewmentioning
confidence: 99%
“…Thus, infiltration of NIPCs/PDCs and expression of IFN␤ and the type I IFN-inducible protein MxA can be detected in the synovia of patients with rheumatoid arthritis (99)(100)(101). Patients with dermatomyositis have a typical IFN gene signature and IFN␣-containing BDCA-2-positive cells in muscle tissue (102,103).…”
Section: The Type I Ifn System In Other Autoimmune Diseasesmentioning
confidence: 99%